1998
DOI: 10.1109/10.668741
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive AR modeling of nonstationary time series by means of Kalman filtering

Abstract: An adaptive on-line procedure is presented for autoregressive (AR) modeling of nonstationary multivariate time series by means of Kalman filtering. The parameters of the estimated time-varying model can be used to calculate instantaneous measures of linear dependence. The usefulness of the procedures in the analysis of physiological signals is discussed in two examples: First, in the analysis of respiratory movement, heart rate fluctuation, and blood pressure, and second, in the analysis of multichannel electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
190
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(199 citation statements)
references
References 23 publications
1
190
0
4
Order By: Relevance
“…Moreover, since vector AR identification may yield unreliable parameter estimates in the presence of noisy data and non-stationary dynamics, variants of the traditional least squares estimators (e.g., exploiting Kalman filters to increase robustness [58] or to track time-varying behaviors [59]) should be considered when these aspects are deemed significant. In the cardiorespiratory data analyzed in this study, good signal-to-noise ratios and stationarity within the observed windows were guaranteed by careful experimental settings and time series measurements and editing, and the linear Gaussian approximation was supported by the knowledge that a conspicuous amount of cardiorespiratory variability can be explained by linear interaction models [6,60].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since vector AR identification may yield unreliable parameter estimates in the presence of noisy data and non-stationary dynamics, variants of the traditional least squares estimators (e.g., exploiting Kalman filters to increase robustness [58] or to track time-varying behaviors [59]) should be considered when these aspects are deemed significant. In the cardiorespiratory data analyzed in this study, good signal-to-noise ratios and stationarity within the observed windows were guaranteed by careful experimental settings and time series measurements and editing, and the linear Gaussian approximation was supported by the knowledge that a conspicuous amount of cardiorespiratory variability can be explained by linear interaction models [6,60].…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we propose Kalman state-space methods [19]- [21] which extend ordinary least-squares (OLS) regression. We consider Kalman methods to be appropriate for CPR artifact removal because:…”
Section: Kalman State-space Methodsmentioning
confidence: 99%
“…We propose a state-space regression model-called adaptive least squares (ALS)-whose states are time-varying regression coefficients and whose observations are the CPR-corrupted ECG signal, cf. [21]. This is a generalization of the aformentioned OLS model having constant coefficients.…”
Section: ) Ordinary Least-squares Regressionmentioning
confidence: 99%
“…The results showed that the MVAR features have a slightly better classification performance and better consistency. Adaptive on-line MVAR was explored in (Arnold et al, 1998), adapting the use of the Kalman filter from the univariate case to the multivariate model. A trivariate AR model of order 22 was used, from which spectral parameters were extracted yielding relevant information regarding neural communication processes.…”
Section: Literature Reviewmentioning
confidence: 99%